In silico investigation and in vivo effect of Berastagi orange (Citrus sinensis) peel extract on male obese rats - Andika Prasetyo; Winda Rizki Pebrina Batubara; Dono Indarto; Tri Nugraha Susilawati (Pharmacia)
Our previous studies show that Berastagi orange peel extract (BOPE) has anti-obesity properties, indicated by its active compounds and effects on reducing body weight gain and body fat percentage. This present study further analysed the effects of BOPE by evaluating docking analysis of BOPE’s phytochemicals and measuring lipid profiles, atherogenic indexes, triglyceride metabolism-related proteins (CD36, DGAT1, and DGAT2) levels, and dipeptidyl peptidase-4 (DPP4) activity in high-fat high-fructose (HFHFr)-induced obese rats. Docking analysis shows that BOPE’s phytochemicals, i.e., naringenin and hesperidin, potentially inhibit CD36 and DGAT1. BOPE significantly reduced LDL cholesterol, triglyceride levels, and DPP4 activity while increasing HDL cholesterol levels. BOPE also improved atherogenic indexes, indicating that BOPE has anti-atherosclerotic and cardioprotective effects. However, no significant effect was observed in the levels of triglyceride metabolism-related proteins, thus warranting further research towards the development of BOPE as a nutraceutical product for obesity prevention and treatment.